2011
DOI: 10.1016/j.bbrc.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenase 1B1 (ALDH1B1) is a potential biomarker for human colon cancer

Abstract: Aldehyde dehydrogenases (ALDHs) belong to a superfamily of NAD(P) + -dependent enzymes, which catalyze the oxidation of endogenous and exogenous aldehydes to their corresponding acids. Increased expression and/or activity of ALDHs, particularly ALDH1A1, have been reported to occur in human cancers. It is proposed that the metabolic function of ALDH1A1 confers the "stemness" properties to normal and cancer stem cells. Nevertheless, the identity of ALDH isozymes that contribute to the enhanced ALDH activity in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 22 publications
4
93
0
1
Order By: Relevance
“…SKNAS iCSCs expressed elevated levels of genes involved in stem cell pathways (NOTCH/DELTA, BMPR/BMP, and FZD/WNT) and genes highly expressed in other CSC types. These include ALDH1B1 (colon carcinoma (20); BIN1, COL1A1, COL1A2, ENPP2, and THY1 (breast CSC-like cells (21); and PDPN (glioblastoma sphere cultures) (22) (Fig. S5 A and B).…”
Section: Short-term Treatments With Epigenetic Modifiers Enhance the mentioning
confidence: 99%
“…SKNAS iCSCs expressed elevated levels of genes involved in stem cell pathways (NOTCH/DELTA, BMPR/BMP, and FZD/WNT) and genes highly expressed in other CSC types. These include ALDH1B1 (colon carcinoma (20); BIN1, COL1A1, COL1A2, ENPP2, and THY1 (breast CSC-like cells (21); and PDPN (glioblastoma sphere cultures) (22) (Fig. S5 A and B).…”
Section: Short-term Treatments With Epigenetic Modifiers Enhance the mentioning
confidence: 99%
“…Studies showed that ALDH1B1 and ALDH1A1 are differentially expressed in normal human tissues, but ALDH1B1 is expressed at higher levels than ALDH1A1 in human epithelial cancers. ALDH1B1 was abundantly expressed in adenocarcinomas originating from the tissue and particularly in colonic adenocarcinoma (Chen, et al, 2011). Thus it can be deduced that ALDH1B1 may be a marker for colon cancer diagnosis.…”
Section: Colon Cancermentioning
confidence: 98%
“…ALDH1B1 is expressed at higher levels than ALDH1A1 in human epithelial cancers. ALDH1B1 was abundantly expressed in adenocarcinomas originating from the tissue and particularly in colonic adenocarcinoma (Chen, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Human ALDH1B1 has an exclusive preference for NAD+ as a cofactor and is catalytically active toward short-and medium-chain aliphatic aldehyde, the product of lipid peroxidation and aromatic aldehyde [26]. For SNP (rs250619092) in DLY pigs, the genotype CC had a higher frequency (CC 79.1%>CA 20.8%), but the individuals with the CA genotype showed a larger daily weight gain (CC 953.07±18.37<CA 1061.46±34.89, P = 0.0059).…”
Section: Growth Traits Sucla2(c/t) Suclg2(c/t) Aldh1b1(c/a)mentioning
confidence: 99%
“…However, our genes of interest have a common function and are involved in certain metabolic diseases [26,[28][29][30], which suggest that functions within chemical and energy metabolism may account for the effects of these genes on growth.…”
Section: Growth Traits Sucla2(c/t) Suclg2(c/t) Aldh1b1(c/a)mentioning
confidence: 99%